Genetic deficiency of aldose reductase counteracts the development of diabetic nephropathy in C57BL/6 mice - Liu, H. (Springer-Verlag, 2011)
AIMS/HYPOTHESIS: The aim of the study was to investigate the effects of genetic deficiency of aldose reductase in mice on the development of key endpoints of diabetic nephropathy. METHODS: A line of Ar (also known as Akr1b3)-knockout (KO) mice, a line of Ar-bitransgenic mice and control C57BL/6 mice were used in the study. The KO and bitransgenic mice were deficient for Ar in the renal glomeruli and all other tissues, with the exception of, in the bitransgenic mice, a human AR cDNA knockin-transgene that directed collecting-tubule epithelial-cell-specific AR expression. Diabetes was induced in 8-week-old male mice with streptozotocin. Mice were further maintained for 17 weeks then killed. A number of serum and urinary variables were determined for these 25-week-old mice. Periodic acid–Schiff staining, western blots, immunohistochemistry and protein kinase C (PKC) activity assays were performed for histological analyses, and to determine the levels of collagen IV and TGF-β1 and PKC activities in renal cortical tissues. RESULTS: Diabetes-induced extracellular matrix accumulation and collagen IV overproduction were completely prevented in diabetic Ar-KO and bitransgenic mice. Ar deficiency also completely or partially prevented diabetes-induced activation of renal cortical PKC, TGF-β1 and glomerular hypertrophy. Loss of Ar results in a 43% reduction in urine albumin excretion in the diabetic Ar-KO mice and a 48% reduction in the diabetic bitransgenic mice (p < 0.01). CONCLUSIONS/INTERPRETATION: Genetic deficiency of Ar significantly ameliorated development of key endpoints linked with early diabetic nephropathy in vivo. Robust and specific inhibition of aldose reductase might be an effective strategy for the prevention and treatment of diabetic nephropathy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00125-011-2045-4) contains supplementary material, which is available to authorised users.